Longitudinal clinical evaluation of adjunct minocycline in the treatment of chronic periodontitis - Cortelli, Jose Roberto; Rodrigues Querido, Silvia Maria; Aquino, Davi Romeiro; Ricardo, Lucilene Hernandes; Pallos, Debora (Amer Acad Periodontology, 2006)
Background: the clinical benefits of minocycline in combination with thorough scaling and root planing (SRP) have been examined in multicenter studies. The aim of this longitudinal investigation was to evaluate the clinical response to scaling and root planing combined with the use of locally delivered minocycline microspheres for 720 days in individuals with advanced chronic periodontitis.Methods: A total of 26 individuals aged 26 to 69 years (mean: 46.8 +/- 12.1 years) were included in this double-blind randomized clinical trial. After randomization, 13 individuals were selected for the test group (TG) and treated with SRP plus subgingival minocycline at baseline and 90, 180, and 270 days, and 13 individuals were selected for the control group (CG) and received SRP plus vehicle at the same time-points. Two homologous sites with probing depth (PD) >= 6 mm were chosen in each subject. To evaluate the clinical response after treatment, PD, plaque index (PI), and gingival index (GI) were assessed at baseline and 90, 180, 270, 360, and 720 days.Results: No statistical differences were found between test and control groups in relation to PD at the different timepoints. The mean values of PD demonstrated a higher reduction in the test group at 270 and 360 days. No statistical differences were observed at 90, 180, and 720 days between TG and CG (P < 0.05; Wilcoxon test). There were no statistically significant differences between TG and CG concerning PI and GI (P < 0.05; analysis of variance and t test) at all evaluated timepoints.Conclusion: Our findings demonstrated that both therapies reduced mean PD from 90 to 360 days; however, SRP combined with the use of subgingival minocycline showed a higher reduction at 270 and 360 days following therapy.
Keywords: clinical trials; minocycline/therapeutic use; periodontitis/therapy